Large carnivore distribution in relationship to environmental and anthropogenic factors in a multiple‐use landscape of Northern Tanzania. (27th June 2018) - Mkonyi, Felix J.; Estes, Anna B.; Lichtenfeld, Laly L.; Durant, Sarah M.
Abstract: Effective management of threatened wildlife, particularly large carnivores, depends on a sound understanding of their spatial distribution and status in relationship to environmental or anthropogenic impacts. Here, we analyse data from spoor surveys to investigate occurrence across a multiple‐use landscape in the Tarangire–Simanjiro ecosystem in northern Tanzania for four taxa of African large carnivores: lions ( Panthera leo ), hyaenas (spotted hyaenas ( Crocuta crocuta) and striped hyaenas (Hyaena hyaena ) combined), cheetahs ( Acinonyx jubatus ) and leopards ( P. pardus ). We analysed our data using occupancy modelling, explicitly accounting for detectability, to identify associations with environmental and anthropogenic variables. Overall occurrence was estimated at 0.85 ( SE  = 0.06) for hyaena, 0.82 ( SE  = 0.15) for cheetah, 0.55 ( SE  = 0.10) for lion and 0.61 ( SE  = 0.21) for leopard. Lion occurrence was negatively associated with distance to park boundary. Hyaena occurrence was positively associated with human population density and negatively associated with bushland, while cheetah and leopard occurrences were positively associated with grassland. These results suggest that lions may be more vulnerable to human impacts than other species, while hyaenas may benefit from vicinity to humans. Our study demonstrates the value of spoor‐based occupancy surveys for understanding distribution and habitat use of secretive large carnivores.